2009
DOI: 10.1111/j.1537-2995.2008.01953.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry for genotyping of human platelet‐specific antigens

Abstract: Compared to conventional methods, the MALDI-TOF MS showed several advantages, such as a high velocity, the ability to perform multiplexed assays in a single reaction, and automated high-throughput analysis of samples. This enables cost-efficient large-scale PLT genotyping for clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Morover, the stability of this automated method makes it suitable as a routine testing tool for genotyping. Although the initial purchase of mass-spectrometric equipment is costly, the running costs for some particular assays, like the methods proposed from the studies of Garritsen et al [53] and Gassner et al [39], can be very low (3.5 cents per genotype). While the whole procedure from sample preparation to automated analysis takes 8-9 hours, there is still much development in regards to the clinical application of this technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Morover, the stability of this automated method makes it suitable as a routine testing tool for genotyping. Although the initial purchase of mass-spectrometric equipment is costly, the running costs for some particular assays, like the methods proposed from the studies of Garritsen et al [53] and Gassner et al [39], can be very low (3.5 cents per genotype). While the whole procedure from sample preparation to automated analysis takes 8-9 hours, there is still much development in regards to the clinical application of this technique.…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on a set of SNPs, blood group genotyping is rapidly evolving, and several MALDI-TOF MS approached have been reported [39,[53][54][55][56][57]. Collaboration studies between Swiss and German researchers have successfully demonstrated the application of MALDI-TOF MS for genotyping foetal SNPs in maternal blood for non-invasive prenatal diagnosis of genetic diseases [54][55][56].…”
Section: Maldi-tof Ms In Transfusion Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…We examined 120 donors by the multiplexed assay and compared the results generated by a sequence-specific primer PCR (SSP-PCR) and conventional sequencing. A 99.7-100% concordance for the genotyping of the 12 HPA alleles between the MALDI-TOF MS assay and conventional methods was achieved [47]. The multiplexed assay allows for the elimination of the time-and cost-consuming gel electrophoresis or fluorescent labelling.…”
Section: Maldi-tof In Nipd Of Fetal Blood Group Genotypingmentioning
confidence: 94%
“…Less than 5% mutant DNA in a more than 95% wild-type DNA background could be precisely discriminated [46]. Recently, multiplexing PCR and extension reactions in a single well with high automation is available to increase the high-throughput capacity and re- duce cost for genotyping [47]. The high-throughput sensitive MALDI-TOF MS has been successfully used for detecting fetal single nucleotide mutations in maternal wild-type DNA allowing for NIPD of genetic diseases [48,49].…”
Section: Maldi-tof Msmentioning
confidence: 99%